Estimation of the Allele Frequency of Type 1 Polysaccharide Storage Myopathy and Malignant Hyperthermia in Quarter Horses in Brazil - Zanzarini Delfiol, Diego Jose (2018)
Type 1 polysaccharide storage myopathy (PSSM1) and malignant hyperthermia (MH) are autosomal dominant genetic diseases caused by a point mutation in equine GYS1 and RYR1, respectively. Although the prevalence of PSSM1 and MH have been described in other countries as causes of myopathy in horses, there are no studies evaluating the allele frequency of those mutations in Brazil. The aim of the present study was to determine the allele frequency of the mutated alleles causing susceptibility for PSSM1 and MH mutations in Quarter Horses (QHs) in Brazil. Deoxyribonucleic acid was purified from blood samples of 741 QHs used in five competitive disciplines (i.e., barrel racing, cutting, halter, racing, and reining). The PCR was optimized to identify the mutations using primers designed from the sequence of equine GYS1 and RYR1. The allele frequencies and the prevalence of PSSM1 were 0.034 and 6.7%, respectively. The highest allele frequency for the GYS1 mutated gene was identified in halter horses (0.163), and the gene mutation was not observed in racing animals. The mutation in the RYR1 was not identified in any of the sampled horses. The PSSM1 allele frequency observed in the present study indicates the relevance of the disease in the differential diagnosis of myopathies in horses. In addition, the absence of the RYR1 causative mutation suggests little importance of MH as a genetic muscle disorder in the Brazilian QHs. (C) 2018 Elsevier Inc. All rights reserved.